HPV Vaccine Status, Gender, Sexual Identities and Risk Behaviors of Adults Residing in Puerto Rico: A Cross-Sectional Study - Pulido, Daisy; Perez-Laras, Linda; Tonkopiy, María; García-Castro, Gabriel; Vélez, Luis A.; Delgado, Yamixa (Puerto Rico Health Sciences Journal, 2024)
Objective: Currently, in Puerto Rico (PR) there is no study for HPV vaccination rates after implementing mandatory HPV vaccination school entry policy in 2018. This study aims to (a) explore HPV vaccination status in adults (≥18 years) residing in PR., particularly those who fall within the age range approved for vaccination; (b) describe participants’ gender and sexual identities and behavior risk factors; and (c) determine how the willingness to vaccinate against HPV is influenced by sociodemographic factors such as age, gender, education level, and health insurance. Methods: We conducted a cross-sectional study to understand HPV vaccination status, sexual health and behavior risk factors, and sociodemographic factors in adults residing in PR. Surveys were distributed using various strategies over six months to collect data. Informed consent was obtained, and participants were assured anonymity and data utilization. We performed descriptive and logistic regression analyses using STATA. Results: From a sample of 314 individuals, 47% were vaccinated, and 82% were familiar with the HPV vaccine. Among the unvaccinated, 49% were open to vaccination. Age and gender significantly predicted vaccination status, with older individuals 65% less likely and females 60% more likely to be vaccinated than males and other genders. Conclusion: This study identifies age, gender identity, education, and health insurance as pivotal determinants of HPV vaccination status in PR. It also found interest in vaccine information among non-vaccinated people, revealing significant coverage disparities crucial for enhancing vaccination rates and sexual health education.